Strengthening Midwives in the Traditional Healthcare Services Program (Yankestrad) in the Working Area of Ingin Jaya Public Health Center, Aceh Besar District - Yuniwati, Cut; Nurdahliana, Nurdahliana; Noviyanti, Noviyanti; Dewi, Ratna; Rimadeni, Yeni (Journal of Midwifery and Nursing, 2024)
Program to Strengthen Midwives in Traditional Healthcare Services (Yankestrad) is an initiative aimed at enhancing the competence and capacity of midwives in providing traditional healthcare services. The program encompasses several key phases, including preparation, implementation, and evaluation. In the initial phase, 30 midwives underwent a refresher training program to ensure they were well-prepared for the subsequent comprehensive training. The program aimed to provide them with a deep understanding of traditional healthcare practices. The results of this community service program (Pengabdian Kepada Masyarakat) clearly indicate that the "Strengthening Midwives in Traditional Healthcare Services Program (Yankestrad)" in the Ingin Jaya Public Health Center (Puskesmas) area of Aceh Besar District has achieved significant milestones. Continuous evaluation conducted both during and after the training has shown remarkable improvements in the participants' abilities to deliver traditional healthcare services. The program has led to enhanced skills in communication and counseling among the midwives, which is crucial in providing effective healthcare services. Additionally, it successfully integrated information technology to augment knowledge, making use of online resources for up-to-date information. The program also delved into deepening the participants' understanding of the local cultural values that underlie traditional healthcare practices. These positive impacts have created substantial changes in the realm of traditional healthcare services and significantly improved the relationships between healthcare providers and patients. The commitment to continuous improvement ensures that this program serves as a solid foundation for further developments in advancing traditional healthcare services.